Classroom English Teaching Practices Integrating Islamic Perspectives in Muslim Minority Madrasah Contexts - Himawati, Ulya; Rinjani, Ersila Devy; Yakin, El; Husna, Muhammad Ahsanul; Sakrany, Man (Register Journal, 2026)
This study explores classroom English teaching practices and the enactment of Islamic perspectives in a Muslim-minority madrasah in Phnom Penh, Cambodia. It addresses the gap between normative discussions of Islamic English Language Teaching and classroom-level evidence by examining the practical implementation of English teaching, the integration of Islamic perspectives during instruction, and the challenges faced by teachers in the classroom setting. Using a qualitative case study design, data were collected through classroom observations, semi-structured interviews with the English teacher, school leaders, and selected students, and document analysis. The findings show strong alignment with the Ministry of Education, Youth and Sport (MoEYS) curriculum and textbook sequencing, resulting in predominantly textbook-centered and form-focused instruction. Islamic perspectives were most visible in classroom routines, greetings, interactional norms, and moral reminders, while they were less evident in instructional content and language-learning tasks. Classroom interaction remained largely teacher-led; student participation was more apparent in task completion than in extended communicative use of English. Interview data indicate that these patterns were shaped by contextual constraints, including mixed-ability learners, limited English foundations, curriculum demands, restricted instructional time, and limited pedagogical space for alternative materials. Overall, this study provides context-sensitive, empirically grounded insights into English teaching in Islamic educational institutions within Muslim minority settings and highlights the need for pedagogical support and flexible curriculum interpretation to strengthen integration of Islamic perspective in task and content design while maintaining alignment with national standards.